Development of a Dimensions Measurement System Based on Depth Camera for Logistic Applications - KÜÇÜK, HALUK (SPIE-INT SOC OPTICAL ENGINEERING, 2019)
In this work a dimension estimation system is developed for logistic applications. The purpose of the system is to find the oriented minimum bounding box of a package. The volume of the bounding box and the volumetric weight of the package were determined. Intel (R) RealSense (TM) Depth Camera D415 was used to obtain point cloud of the package view. Then smoothing and filtering algorithms were applied to eliminate the noise and the distortion. The object is isolated from the background and the minimum bounding box is determined. Different geometric shapes were tested including: hardboard calibrated cube, cube with an uneven top, uncalibrated box, cube with a sloped side, small cylinder, tube and cylinder with irregular top. Statistical analysis of the measurements revealed an average error rates less than 0.5cm for normal work conditions. This error rate is acceptable for most logistic operations.
Keywords: 3D depth camera; logistics; Intel (R) RealSense (TM); D415; dimensioning system; cubing; automatic dimension measurement